The emergence of Caryospora neofalconis in falcons in Central Saudi Arabia - Alfaleh, Faleh; Alyousif, Mohamed; Elhaig, Mahmoud (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to examine the occurrence of Caryospora (C.) neofalconis in falcons from the central region of the Kingdom of Saudi Arabia (KSA). Materials and methods: Fecal samples (n = 149) from 149 healthy falcons including 56 saker falcons (Falco cherrug), 13 lanner falcons (F. biarmicus), 18 peregrine falcons (F. peregrinus), 40 Barbary falcons (F. pelegrinoides), and 22 gyrfalcons (F. rusticolus) were collected between October 2018 and May 2019. The fecal samples were examined for the presence of C. neofalconis by microscopic examination followed by confirmation by polymerase chain reaction targeting 18S rRNA genes and their phylogenetic analyses. Results: The overall prevalence of C. neofalconis in the falcons was recorded as 10.7% (16/149) by microscopic examination. The highest prevalence was found in F. peregrinus (6/18, 33.3%), followed by F. rusticolus (3/22, 13.6%), F. cherrug (5/56, 8.9 %) and F. pelegrinoides (2/40, 5.0%). There was no C. neofalconis infection observed in F. biamicus. The 18S rRNA gene could be amplified in eight samples. The phylogenetic analysis of two C. neofalconis isolates exhibited a close relationship with the Mexican isolate (KT03081) with a 99.7% identity. Conclusions: To our knowledge, based on the microscopic and molecular analysis, this is the first report of C. neofalconis in F. cherrug, F. rusticolus, F. pelegrinoides, and F. peregrinus from the central region of the KSA and it emphasize the value of adopting preventive measures to limit the spread of C. neofalconis. J. Adv. Vet. Anim. Res., 7(3): 530-536, Sep 2020 http://doi.org/10.5455/javar.2020.g450